2012
DOI: 10.1007/s13191-012-0223-9
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro investigation to compare the surface roughness of auto glazed, reglazed and chair side polished surfaces of Ivoclar and Vita feldspathic porcelain

Abstract: The change in surface roughness after different surface finishing techniques has attracted the attention of several prosthodontists regarding wear of opposing teeth or restorative material and the strength; plaque retention and appearance of the restoration. However, there is considerable controversy concerning the best methods to achieve the smoothest and strongest porcelain restorations after chair side clinical adjustments. The purpose of this in vitro study was to compare the average surface roughness of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
5
14
0
3
Order By: Relevance
“…These findings are in agreement with previous reports . The glaze produces a smooth and regular surface with less wear to antagonist enamel and restoration and less plaque accumulation . The layered digital group (TriLuxe forte) demonstrated the highest Ra and Rz values at the glazed stage.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings are in agreement with previous reports . The glaze produces a smooth and regular surface with less wear to antagonist enamel and restoration and less plaque accumulation . The layered digital group (TriLuxe forte) demonstrated the highest Ra and Rz values at the glazed stage.…”
Section: Discussionsupporting
confidence: 92%
“…The final polishing with diamond paste did not show a significant reduction in surface roughness of monolithic and veneered zirconia, which was also in agreement with previous studies . Contrary to this, other studies have shown that diamond paste improved the surface smoothness of some ceramic restorations . These differences with other studies could be related to the different types of ceramic restorations used in this study and the protocol of finishing and polishing.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations